The accuracy of Hopkins Symptom Checklist – 25 (HSCL-25) depression subscales (Indonesian version) on adolescents - Ayu Rahmawati Tirto; Sherly S. Turnip (HUMANITAS: Indonesian Psychological Journal, 2019)
Hopkins Symptom Checklist - 25 (HSCL-25) depression subscale is an easy-to-use and mainstream screening tool to detect symptoms of an early stage depression, including for adolescents. Previous studies conducted all over the countries indicated that HSCL-25 has relatively good accuracy. However, there remains to be no accuracy testing of the HSCL-25 in Indonesia. Our study aimed to examine the accuracy of HSCL-25 depression subscales (Indonesian version) in contrast to the semi-structured diagnostic interview as the gold standard. This is a non-experimental study by conducting a diagnostic interview on 40 participants. The diagnostic status obtained from the interviews was then compared to the HSCL-25 scores from the previous study. We analyzed the data using cross-tabulation, Pearson, chi-square, and Receiver Operatic Characteristics (ROC) analysis to obtain the accuracy and optimum cut-off score. Our findings show that HSCL-25 depression subscales have good sensitivity and fairly good specificity. The cut-off score used in this study was optimum to be used as a cut-off point in the prevention context. Thus, we conclude that, with the current optimum cut-off score, HSCL-25 depression subscale is a reasonably good instrument for detecting symptoms of early depression among adolescents.